ANALISIS KESANTUNAN DALAM TEKS PAWARTA PADA MAJALAH PANJEBAR SEMANGAT TAHUN 2015 DAN RELEVANSINYA SEBAGAI MATERI AJAR MENELAAH TEKS BERITA SISWA KELAS VIII SMP - Pratiwi, Mashita Dian; Anindyarini, Atikah; Rahmat, Rahmat (Universitas Sebelas Maret, 2017)
The purposes of this research are to describe:(1) form of politeness in news text in the Panjebar Semangat Magazine in 2015; (2) the relevance of news text in Panjebar Semangat magazine for teaching material’s review news text for 8th grade students of Junior High School/ Secondary School.Based on this research, it can be concluded that: (1) form of politeness in ten news text Panjebar Semangat Magazine consist of politeness principle and the most widely found is sympathy maxim, and the generosity maxim could not be found. For politeness scale, the most widely found is indirect scale, and the least used is optionally scale. On violation of the principle of politeness, the most widely found is aprobiation maxim and the least are generosity maxim and sympathy maxim, (2) politeness analysis in news text Panjebar Semangat magazine in 2015 are relevance to be used as teaching materials on news text review for 8th grade students of junior high school.